Redefining Market Dynamics: A Bibliometric Lens on Innovation and New Product Strategy Trends - Safitri, Wiji; Agus Rahayu; Heny Hendrayati (Yayasan Sinergi Kawula Muda, 2025)
Innovation and New Product Strategy are an important part of the marketing world. Increasingly dynamic consumers and increasingly competitive markets, companies are required to carry out Innovation and New Product Strategy. This is in line with the increasing publication results over the past five years on this theme. Companies need a direction for innovation and new product strategy. In addition, newness is needed in innovation and new product strategy. This study aims to identify trends regarding Innovation and New Product Strategy in Marketing. Furthermore, to find newness in the theme. This study uses bibliometric analysis to find trends and newness in research on Innovation and New Product Strategy in marketing. Samples were obtained from Scopus data with the keyword Innovation and New Product Strategy in Marketing. Publications were determined in the last five years and the keywords that were limited were only for marketing. 148 documents were obtained that met the criteria for this research sample. The results of this study are research trends towards entrepreneurship and social media. While the newness for further research can connect the keyword customer behavior and new product development with the theme of Innovation and new product strategy, especially in the context of marketing.